1999
DOI: 10.1144/0050117
|View full text |Cite
|
Sign up to set email alerts
|

The origin and genesis of major Jurassic unconformities within the triple junction area of the North Sea, UK

Abstract: Three Jurassic unconformities of intra-Aalenian, intra-Callovian and intra-middle Oxfordian age are consistently identified within the literature for the North Sea region but despite their common recognition these unconformities remain poorly understood and they are essentially spatially and temporally unconstrained. The recent development of a sequence stratigraphic framework for the Jurassic of the North Sea allows for a thorough investigation of the spatial and temporal characteristics of the intra-Callovia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…Subsequently, Thomas & Coward (1995), working in the Northern North Sea, have suggested that a Bathonian to Kimmeridgian phase of NW-SE oriented regional extension was superceeded by a separate phase of NE-SW extension in the latest Jurassic to Early Cretaceous, which placed older features, such as the Viking Graben, in sinistral shear. A similar model has been proposed for the Central North Sea area by Davies et al (1999) who proposed W-E extension in the end Bathonian/early Callovian, NW-SE extension in the Middle Oxfordian to Early Kimmeridgian and finally NE-SW extension in the Late Kimmeridgian and Volgian.…”
Section: Late Jurassic)early Cretaceoussupporting
confidence: 64%
See 1 more Smart Citation
“…Subsequently, Thomas & Coward (1995), working in the Northern North Sea, have suggested that a Bathonian to Kimmeridgian phase of NW-SE oriented regional extension was superceeded by a separate phase of NE-SW extension in the latest Jurassic to Early Cretaceous, which placed older features, such as the Viking Graben, in sinistral shear. A similar model has been proposed for the Central North Sea area by Davies et al (1999) who proposed W-E extension in the end Bathonian/early Callovian, NW-SE extension in the Middle Oxfordian to Early Kimmeridgian and finally NE-SW extension in the Late Kimmeridgian and Volgian.…”
Section: Late Jurassic)early Cretaceoussupporting
confidence: 64%
“…This was interrupted in the Toarcian-Aalenian, probably by the growth and subsequent deflation of a thermally-induced crustal dome centred in the east of the study area (Eynon 1981;Ziegler 1982;Underhill & Partington 1993;Davies et al 1999), which was associated with Bathonian-Callovian volcanism (Forties Volcanic Province; Smith & Ritchie 1993;White & Latin 1993). The age and dimensions (c. 1250 km radius) of this Mid North Sea dome (Ziegler 1982) have been documented by Underhill & Partington (1993) using sequence stratigraphy and analysis of the erosion pattern of the widespread 'Mid Cimmerian unconformity' associated with this event.…”
Section: Middle Jurassicmentioning
confidence: 99%
“…Together with a global regression, the consequence was that the seaway connecting the Boreal and Tethys seas was blocked causing deep erosion of Early Jurassic and older sediments (Vail et al, 1977;Ziegler, 1992). Hence, there is a marked unconformity (the midCimmerian or intra-Aalenian unconformity) separating the Lower Jurassic from the Middle and Upper Jurassic in the region (Davies et al, 1999) (Fig. 3).…”
Section: Sampling Procedures and Methodsmentioning
confidence: 99%
“…They considered the amount of uplift associated with the transient mantle plume to have been in the region of 400 -500 m, somewhat less than earlier estimates. Davies et al (1999) highlighted the minimal impact of the deflating dome on the stratigraphic architecture of the succeeding Late Jurassic rift. Underhill and Partington's (1993) detailed stratigraphic correlations and analyses demonstrated the regional overstep of the Middle and Late Jurassic across the unconformity, truncation patterns to the north and west, facilitated by the well-constrained stratigraphies of the Viking Graben and Inner Moray Firth respectively.…”
Section: The 'Mid Cimmerian' and Controls On Effective Triassic Resermentioning
confidence: 99%